Assessment of Thyroid Function Status and Thyroid Antibody Levels Among Tribal Population of Jarugumalai Hills of Salem District, Tamil Nadu, India - Vijayakarthikeyan M; Arul Prakash S; Prema Priya G; Angayarkanni P (Medsci Publications, 2024)
Background: Tribal population not only suffers from malnutrition and communicable diseases but also from non-communicable diseases. Globally, one of the most frequent metabolic disorders include thyroid disorders.  The study was conducted to estimate the prevalence of Thyroid disorders using Thyroid Function Test, to determine the Anti-Thyroid Peroxidase Antibody levels among the tribal population, and also to determine the factors associated with thyroid disorders among the tribal population. Materials and Methods: It is a community based analytical cross-sectional study conducted among 375 tribal residents of Jarugumalai hills. Data was collected using a pre tested semi-structured questionnaire. Categorical variables were described using frequency and percentage. Variables significantly associated with thyroid disorders were identified using univariate and multivariate analysis. Results: Nearly 32% had any form of thyroid disorders. About 18% and 7% respectively had subclinical hypothyroidism and overt hypothyroidism. Also, 12% of the study participant blood samples were positive for Anti Thyroid Peroxidase antibody (ATPO). Female gender Usage of inadequately iodised salt and presence of ATPO were significantly associated with thyroid disorder on multivariate analysis. Conclusion: Thyroid status assessment showed a high prevalence (32%) among the marginalized population. Multi-pronged approach involving educational, administrative and legal measures must be implemented to curb this problem.